Diagnostic performance of the Bosniak classification, version 2019 for cystic renal masses: A systematic review and meta-analysis - Zhang, Qing; Dai, Xiaoli; Li, Wei (Frontiers in Oncology, 2022)
Purpose: To systematically assess the diagnostic performance of Bosniak version 2019 for risk stratification of cystic renal masses. Methods: We conducted an electronic literature search on Web of Science, MEDLINE (Ovid and PubMed), Cochrane Library, EMBASE, and Google Scholar to identify relevant articles from 2019 until March 31, 2022. We included studies using the Bosniak version 2019 for risk stratification of cystic renal masses. Summary estimates of sensitivity, specificity, positive likelihood ratio (LR+), negative likelihood ratio (LR−), and diagnostic odds ratio (DOR) were pooled with the bivariate model and hierarchical summary receiver operating characteristic (HSROC) model. The quality of the included studies was assessed with the Quality Assessment of Diagnostic Accuracy Studies-2 tool. Results: A total of 7 studies comprising 657 patients were included in the current meta-analysis. The pooled sensitivity and specificity were 0.86 (95% CI 0.78–0.91) and 0.65 (95% CI 0.54–0.73) for the threshold of category III/IV, with the calculated area under the HSROC curve of 0.83 (95% CI 0.79–0.86). The pooled LR+, LR−, and DOR were 2.44 (95% CI 1.84-3.25), 0.22 (95% CI 0.14–0.35), and 11.1 (95% CI 5.8-21.1), respectively. The Higgins I2 statistics demonstrated substantial heterogeneity across studies, with I2=62.4% for sensitivity and I2=78.0% for specificity. In 7 studies performing head-to-head comparison, the Bosniak classification 2019 demonstrated significantly higher pooled specificity (0.62 vs. 0.41, P<0.001) than version 2005, however, the pooled sensitivity of the new version was significantly lower (0.88 vs. 0.94, P=0.001). Conclusions: The Bosniak classification version 2019 has high sensitivity but moderate specificity, and there was no difference in diagnostic accuracy between CT and MRI. As compared to version 2005, Bosniak version 2019 could significantly reduce unnecessary biopsies and overtreatment but at the cost of a substantial decline in sensitivity.